Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

P30-49 Hazard assessment of endocrine disruption potential using new alternative methods: integration of in vitro thyroid peroxidase inhibition potency and metabolic fate of 3-amino-2,6-dimethylphenol explains its lack of thyroid toxicity in vivo - K.C. Fussell; S. Verkaart; J. van den Elzen; N. Pineiro Costas; M. Pavan; C. Novello; B. Blömeke; M. Wenker; C. Goebel (Toxicology Letters, 2025)

P28-31 Diverging endocrine disruption potential of resorcinol and paracetamol: profiling the endocrine disruption potential of these compounds and their metabolites using in silico methods - C. Novello; M. Pavan; K. Fussell; C. Goebel (Toxicology Letters, 2025)

P07-02 Safety evaluation of hair straightening products containing glyoxylic acid assessing formaldehyde release and oxalic acid formation - G. von Bölcsházy; N. Hewitt; C. Schmidt; S. Langhoff; C. Goebel (Toxicology Letters, 2025)

P28-18 Diverging endocrine disruption potential of resorcinol and paracetamol: thyroid peroxidase inhibition potency and metabolic fate differences under pharmaceutical and cosmetic use explain their contrasting endocrine disruption capabilities - K.C. Fussell; S. Verkaart; J. van den Elzen; M. Pavan; C. Novello; B. Blomeke; M. Wenker; C. Goebel (Toxicology Letters, 2025)

Explainable machine learning for labquake prediction using catalog-driven features - Sadegh Karimpouli; Danu Caus; Harsh Grover; Patricia Martínez-Garzón; Marco Bohnhoff; Gregory C. Beroza; Georg Dresen; Thomas Goebel; Tobias Weigel; Grzegorz Kwiatek (Earth and Planetary Science Letters, 2023)

The effects of mixed-species root zones on the resistance of soil bacteria and fungi to long-term experimental and natural reductions in soil moisture - Roland C. Wilhelm; Juana Muñoz-Ucros; Fabian Weikl; Karin Pritsch; Marc Goebel; Daniel H. Buckley; Taryn L. Bauerle (Science of The Total Environment, 2023)

Litter quality and decomposition responses to drought in a northeastern US deciduous forest - Alexis M. Wilson; James C. Burtis; Marc Goebel; Joseph B. Yavitt (Oecologia, 2022)

Reconstructing imagined letters from early visual cortex reveals tight topographic correspondence between visual mental imagery and perception - Mario Senden; Thomas C. Emmerling; Rick van Hoof; Martin A. Frost; Rainer Goebel (Brain Structure and Function, 2019)

Novel anelloviruses identified in buccal swabs of Antarctic fur seals - Adele Crane; Michael E. Goebel; Simona Kraberger; Anne C. Stone; Arvind Varsani (Virus Genes, 2018)

A Comparison of Seismicity Characteristics and Fault Structure Between Stick–Slip Experiments and Nature - T. H. W. Goebel; C. G. Sammis; T. W. Becker; G. Dresen; D. Schorlemmer (Pure and Applied Geophysics, 2015)

Genes expressed by the biological control bacterium P seudomonas protegens Pf ‐5 on seed surfaces under the control of the global regulators GacA and RpoS - Teresa A. Kidarsa; Brenda T. Shaffer; Neal C. Goebel; Daniel P. Roberts; Jeffrey S. Buyer; Aaron Johnson; Donald Y. Kobayashi; T. Mark Zabriskie; Ian Paulsen; Joyce E. Loper (Environmental Microbiology, 2013)
Summary Gene expression profiles of the biological control strain P seudomonas protegens Pf ‐5 inhabiting pea seed surfaces were revealed using a whole‐genome oligonucleotide microarray. We identified genes expressed by Pf ‐5 under the control of two global regulators ( GacA and RpoS ) known to influence biological control and secondary metabolism. Transcript levels of 897 genes, including many with unknown functions as well as those for biofilm formation, cyclic diguanylate (c‐di‐ GMP ) signalling, iron homeostasis and secondary metabolism, were influenced by one or both regulators, providing evidence for expression of these genes by Pf ‐5 on seed surfaces. Comparison of the GacA and RpoS transcriptomes defined for Pf ‐5 grown on seed versus in broth culture overlapped, but most genes were regulated by GacA or RpoS under only one condition, likely due to differing levels of expression in the two conditions. We quantified secondary metabolites produced by Pf ‐5 and gacA and rpoS mutants on seed and in culture, and found that production profiles corresponded generally with biosynthetic gene expression profiles. Future studies evaluating biological control mechanisms can now focus on genes expressed by Pf ‐5 on seed surfaces, the habitat where the bacterium interacts with seed‐infecting pathogens to suppress seedling diseases.

Inactivation of the GacA response regulator in Pseudomonas fluorescens Pf‐5 has far‐reaching transcriptomic consequences - Karl A. Hassan; Aaron Johnson; Brenda T. Shaffer; Qinghu Ren; Teresa A. Kidarsa; Liam D. H. Elbourne; Sierra Hartney; Robert Duboy; Neal C. Goebel; T. Mark Zabriskie; Ian T. Paulsen; Joyce E. Loper (Environmental Microbiology, 2010)
Summary The GacS/GacA signal transduction system is a central regulator in Pseudomonas spp., including the biological control strain P. fluorescens Pf‐5, in which GacS/GacA controls the production of secondary metabolites and exoenzymes that suppress plant pathogens. A whole genome oligonucleotide microarray was developed for Pf‐5 and used to assess the global transcriptomic consequences of a gacA mutation in P. fluorescens Pf‐5. In cultures at the transition from exponential to stationary growth phase, GacA significantly influenced transcript levels of 635 genes, representing more than 10% of the 6147 annotated genes in the Pf‐5 genome. Transcripts of genes involved in the production of hydrogen cyanide, the antibiotic pyoluteorin and the extracellular protease AprA were at a low level in the gacA mutant, whereas those functioning in siderophore production and other aspects of iron homeostasis were significantly higher in the gacA mutant than in wild‐type Pf‐5. Notable effects of gacA inactivation were also observed in the transcription of genes encoding components of a type VI secretion system and cytochrome c oxidase subunits. Two novel gene clusters expressed under the control of gacA were identified from transcriptome analysis, and we propose global‐regulator‐based genome mining as an approach to decipher the secondary metabolome of Pseudomonas spp.

Determining Reference Ecosystem Conditions for Disturbed Landscapes within the Context of Contemporary Resource Management Issues - P. Charles Goebel; Thomas C. Wyse; R. Gregory Corace III (Journal of Forestry, 2005)

Invasion by Toxoplasma gondii protects human-derived HL-60 cells from actinomycin D-induced apoptosis - S. Goebel; C. G. K. Lüder; U. Gross (Medical Microbiology and Immunology, 1999)

Prototyping a Vision for Inter-Agency Terrestrial Inventory and Monitoring: a Statistical Perspective - Carol C. House; J. Jeffery Goebel; Hans T. Schreuder; Paul H. Geissler; William R. Williams; Anthony R. Olsen (Environmental Monitoring and Assessment, 1998)